Gene therapy genetic aspects and possibilities for degenerative diseases of intervertebral disks treatment - Pedachenko, E. G.; Horbatyuk, K. I. (Ukrainian Neurosurgical Journal, 2008)
At the beginning of 90th past century, due to intensive development of molecular biology and tissue engineering, knowledge accumulation about growth factors influence on the intervertebral disc cells, became possible. For the last few years, there were made a lot of experimental works dedicated to the growth factors, and their combination with gene therapy for intervertebral disc biological regeneration. The study of gene therapy possibilities becomes more interesting and perspective, as potentially becomes possible not only to stop the progress of intervertebral disc degeneration, but also to its regeneration. We showed basic principles and pre-conditions for this method study, and also described the main experimental and clinical research studies. Positive results of the investigations enabled to forecast the changes in spine degenerative diseases surgery in the future, making it less invasive and more effective.